Black Politics in Transition - David Covin (2018)
Black Politics in a Time of Transition appears at an historic point in American politics. From the vantage point of the maturation of the study of black politics, this volume provides a framework for current and future discussion of this critical time. Incorporating the expanded stream of work on today's black politics, this latest volume of the National Political Science Review is also a new assessment of the period from which the study of black politics emerged.